Facile Preparation of CeO2 Supported on Graphene Oxide Sheets for NH3‐SCR: Improvement of Catalytic Activity and SO2 Tolerance. Issue 19 (22nd May 2021) - Zhou, Zhiyuan; Wang, Yongzhao; Yuan, Qunfu; Guo, Yanle; Guo, Wenyao; Xin, Zhiling; Zhang, Bingsen; Guo, Ruitang
Abstract: In this paper, a series of highly dispersed CeO2 catalysts on graphene oxide sheets (GO) were prepared by simple impregnation method. The catalysts were applied for selective catalytic reduction(SCR) of NO with NH3 . Compared with the 5 wt %CeO2 /GO and 15 wt %CeO2 /GO catalysts, 10 wt %CeO2 /GO catalyst exhibited better catalytic performance in the temperature range of 175–325 °C and higher SO2 resistance at 275 °C. The as‐prepared catalysts were characterized by TEM, AFM, XPS, XRD, BET, H2 ‐TPR, NH3 ‐TPD and FT‐IR, respectively. The characterization results indicated that 10 wt %CeO2 /GO catalyst possessed larger specific surface area, enriched surface acidic sites, high redox capacity and oxygen vacancies. In addition, Ce 3+ on the surface of CeO2 /GO catalyst could reduce the oxidation property of SO2, thus improving the SO2 resistance of the catalyst. Meanwhile, the stability of 10 wt %CeO2 /GO catalyst was tested. At 275 °C, the NO conversion maintained at 94 % within 30 hours, suggesting the excellent stability. Abstract : A series of highly dispersed CeO2 /GO catalysts were prepared. 10wt %CeO2 /GO catalyst exhibited better catalytic performance in the temperature range of 175–325°C and higher SO2 resistance at 275 °C. The results indicate that 10wt %CeO2 /GO catalyst possesses larger specific surface area, enriched surface acidic sites and high redox capacity. Ce 3+ on the surface of CeO2 /GO catalyst can reduce the oxidation property of SO2, thus improving the SO2 resistance of the catalyst.